Electronic Servicing And Repairs - Linsley, Trevor (Oxford : Newnes, 2000)
This third edition updates the previous text by taking into account changes in the City and Guilds courses 2360 and 2240. It also features hardware topics, an expanded chapter on testing and fault diagnosis, PLCs and CAD software, and new chapters.
Previous ed.: published as Electronics for electricians and service engineers. London: Edward Arnold, 1993.
Includes index.
Keywords: Electronic apparatus and appliances -- Maintenance and repair; Technology